Analyzing Legal Drafting: Legal Discourse Study on Crimes against Women in Pakistan - Khan, Fariah Farooq; Khaleel, Badriah (Pakistan Languages and Humanities Review, 2024)
The primary objective of this research is to examine the legal discourse employed in drafting related to crimes against women, specifically focusing on reported cases. This qualitative study entails the analysis of legal drafting, incorporating interviews with judges. Applying Fairclough's three-dimensional model for analysis, the research reveals that while legal language has its unique format, it often carries stereotypical implications favouring men, possibly influenced by Pakistan's deeply ingrained patriarchal system. Despite notable changes in language and laws favouring women over the past two decades, patriarchal dominance remains a significant barrier to women seeking justice. Respecting the rights and dignity of all litigants is crucial for a fair legal system, fostering equality and justice in the courtroom discourse of Pakistan. Crimes against women in Pakistan persist as a concerning issue, encompassing various forms of violence and discrimination. Addressing this challenge requires concerted efforts in legal frameworks, societal awareness, and support systems for victims.